EFEK PROBIOTIK Candida utilis PENAMPILAN PRODUKSI BURUNG PUYUH PETELUR (Coturnix coturnix japonica) - Eko Widodo; Osfar Sjofjan; Roro Rianthie Jessieca A.G (Universitas Islam Kadiri, 2019)
The aim of this research was to examine effect of addition of Candida utilis probiotic into the feed on quail production performances. The materials used were layer quails of 3 months old, as many as 250 birds, each unit consisted of 10 birds. The method used in this research was feeding trial with 5 treatments and 5 replications. Feeds used were commercial concentrate and Candida utilis probiotic. The feed treatments consisted of P0 = based feed, P1 = based feed with 0,1% Candida utilis, P2 = based feed with 0,2% Candida utilis, P3 = based feed with 0,3% Candida utilis, P4 = based feed with 0,4% Candida utilis. The variables measured were production performances including feed intake, Hen Day Production (HDP), egg mass, feed conversion, and Income Over Feed Cost (IOFC). Data were tabulated in MS. Excel, and analyzed using ANOVA of Completely Randomized Design (CRD), if there were significant effect among the treatments then tested by Duncan’s Multiple Range Test (DMRT). The results showed that the addition of Candida utilis probiotic into the feed had no significant effect on quail production performances including feed intake, HDP, egg mass, feed conversion, and IOFC. It can be concluded that the effect of addition of Candida utilis probiotic did not improve quail production performance including feed intake, HDP, egg mass, feed conversion, and IOFC. It was suggested to use 0,1% Candida utilis in quail feed due to the highest IOFC (IDR 70,8756±15,815 /head/day).